Case Report: The ectopic pancreas in the adrenal glands: It was found due to elevated blood pressure and initially diagnosed as adrenal adenoma - Zhang, Tao; Yin, Si-fan; Wang, Qi-wu; Feng, Wen-bo; Ke, Chang-xing (Frontiers in Surgery, 2022)
Background The ectopic pancreas is a kind of congenital malformation formed during embryonic development, which has no anatomical relationship with the normal pancreas and is a rare solid disease. The ectopic pancreas in the adrenal glands is extremely rare. Case summary A 32-year-old man was admitted to the hospital after experiencing elevated blood pressure for 2 years as well as dizziness and blurred vision for 2 weeks. He had an elevated blood pressure of 170/110 mmHg (1 mmHg = 0.133 kPa) on physical examination 2 years ago, without palpitations, chest pain, and chest tightness. Two weeks ago, he presented with dizziness and blurred vision. Blood renin and aldosterone levels were elevated. Plain CT and contrast-enhanced CT scan showed nodular thickening of the left adrenal and homogeneous enhancement, which was initially considered adrenal adenoma. The postoperative pathology supported the ectopic pancreas in the left adrenal. After 78 months of postoperative follow-up, no recurrence was observed, but his blood pressure remained persistently high. Conclusion The ectopic pancreas occurring in the adrenal glands is extremely rare, has no specific clinical symptoms, and is mainly found for other reasons. It can easily be misdiagnosed as an adrenal adenoma. The final confirmation of the diagnosis still depends on the pathological biopsy. A great deal of reporting is still required for whether there is a correlation with elevated blood pressure.